3D (3-dimensional) porous silver nonwoven mats prepared with cellulosic templates and spray equipment for use as supercapacitor current collectors. (15th December 2015) - Jang, Yunseok; Jo, Jeongdai; Choi, Young-Man; Kwon, Sin; Kim, Kwang-Young
Abstract: We developed a simple method for fabricating a 3D (3-dimensional) porous Ag nonwoven mat for use as the current collector in supercapacitors, and investigated the supercapacitive properties of this mat using cyclic voltammetry. The specific capacitance of an activated carbon electrode on the 3D porous Ag nonwoven mat was 1.24 times greater than that observed for an activated carbon electrode on a conventional 2D (2-dimensional) Ag plate. Additionally, the system with the 3D porous Ag nonwoven mat showed a lower charge transfer resistance of the AC (activated carbon) electrode. These findings demonstrate that the 3D porous Ag nonwoven mat is suitable for use as the current collector in supercapacitors. Graphical abstract: Highlights: Porous Ag was fabricated with simple spray equipment and a cellulosic template. We demonstrated the usefulness of the porous Ag as a current collector. An electrode on the porous Ag had 1.24 times greater capacitance than that on a flat Ag plate.